An updated insight into the effect of β-adrenergic receptor antagonists (β-blockers) on respiratory function in asthma patients: a systematic review and meta-analysis - Marko, Monika; Pawliczak, Rafał (Frontiers in Physiology, 2025)
BackgroundThis study aimed to provide an updated assessment of the changes in respiratory function after β-adrenergic receptor antagonists (β-blockers) administration in asthma patients. The main assumption of the study was to use new methodological and statistical approaches not previously applied in this field in systematic reviews and meta-analyses.MethodsTo select studies, PubMed/Medline, Embase, ClinicalTrials.gov, and Cochrane Library were searched. Additionally, Google Scholar was searched for gray literature. A systematic review and meta-analysis for forced expiratory volume in 1 second (FEV1) and peak expiratory flow rate in asthma patients after administration of cardio-selective and non-selective β-blockers compared to placebo or baseline was performed. We also assessed FEV1 after topical β-blocker application compared to baseline.ResultsAn independent subgroup analysis demonstrated significantly higher FEV1 in the placebo group (standardized mean difference [SMD] =−0.74, 95% confidence interval [CI]: 1.15, −0.34, P = 0.0003) than in non-selective β-blockers. The test for subgroup differences indicates that there is a statistically significant subgroup effect among cardio-selective and non-selective β-blockers (P = 0.03, I2 = 80%). We also showed a statistically significant decrease in FEV1 (SMD = −0.70, 95% CI: [−1.56 to −0.03], P = 0.04) after topical β-blocker application.ConclusionPatients with asthma may tolerate cardio-selective β-blockers better than non-selective β-blockers. The FEV1 value depends on the type of β-blocker used. Cardio-selective β-blockers may be cautiously considered in patients with asthma only when strong cardiovascular indications exist (such as heart failure with reduced ejection fraction or post-myocardial infarction) and with appropriate monitoring. At the same time, less risky therapeutic options should be chosen instead of topical β-blockers.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier 42024606876.